Answer:
<h2>C. G(x) = (x - 1)² - 3</h2>
Step-by-step explanation:
f(x) + n - shift the graph of f(x) n units up
f(x) - n - shift the graph of f(x) n units down
f(x - n) - shift the graph of f(x) n units to the right
f(x + n) - shift the graph of f(x) n units to the left
===================================
Look at the picture.
The graph of F(x) shifted 1 unit to the right and 3 units down.
Therefore the equation of the function G(x) is
![G(x)=(x-1)^2-3](https://tex.z-dn.net/?f=G%28x%29%3D%28x-1%29%5E2-3)
Answer:
A B and E
Step-by-step explanation:
Answer:
8/32=0.25
Step-by-step explanation:
B. Sandwich costs $7.70 and the soda costs $2.20